Square Wave Voltammetric Analysis of Triphenyltin(IV) Hydroxybenzoate Derivatives - Insan Qudus, Hardoko; Dwi Yunita, Ria; A. Kisw, Agung; Hadi, Sutopo (Asian Journal of Chemistry, 2020)
In present work, a chemical analysis of two newly synthesized compounds, triphenyltin(IV) o-hydroxybenzoate (1) and triphenyltin(IV) m-hydroxybenzoate (2) have been performed by using square wave voltammetry (SWV). The method used was validated using the standard solutions of compound 1 and 2 by varying the concentrations. The concentrations of 1.6 × 10-4 M; 3.2 × 10-4 M; 4.8 × 10-4 M; 6.4 × 10-4 M and 8.0 × 10-4 were used in the variations. The validation results of compound 1 were the linear regression equation: ip = 7.42 C + 7.89; correlation coefficient (r) = 0.991; limit of detection (LOD) = 1.53 × 10-4 M; and sensitivity (S) = 7.42 μA/ mM, while compound 2 gave the value of linear regression equation: ip = 8.39 C + 7.91; correlation coefficient (r)= 0.991; limit of detection (LOD)= 1.35 × 10-4 M; and sensitivity (S)= 8.39 μA/mM.